Stock identification methods : applications in fishery science - Cadrin, Steven X.; Friedland, Kevin D.; Waldman, John R. (Elsevier Academic Press, 2005)
Stock Identification Methods is a comprehensive review of the various disciplines used to study the population structure of fishery resources. It represents the experience and perspectives of worldwide experts on each method, assembled through a working group of the International Council for the Exploration of the Sea. The book is organized to foster multidisciplinary analyses and interdisciplinary conclusions about stock structure, a crucial topic for fishery science and management. Technological advances have promoted the development of stock identification methods in many directions, resulting in a confusing variety of approaches. Based on basic tenets of population biology and management needs, Stock Identification Methods offers a unified framework for understanding stock structure using various methods, by promoting an understanding of the relative merits and sensitivities of each approach. * Describes eighteen distinct approaches to stock identification grouped into sections on life history traits, environmental signals, genetic analyses, and applied marks * Features experts' reviews of benchmark case studies, general protocols, and the strengths and weaknesses of each identification method * Reviews statistical techniques for exploring stock patterns, testing for differences among putative stocks, stock discrimination, and stock composition analysis * Focuses on the challenges of interpreting data and managing mixed-stock fisheries.